Penggambaran Eksploitasi Hewan dan Lingkungan dalam Novel “O” Karya Eka Kurniawan - Wulandari, Kurnia (Universitas Islam Sumatera Utara, 2025)
This study investigates the representations of animal and environmental exploitation in the Indonesian novel O by Eka Kurniawan (2016) through the lens of ecocritical theory. The research is motivated by the increasing concern over human domination of nature, often expressed through acts of exploitation that disregard ecological balance. The central research question explores how characters within the novel engage with animals and their surroundings and how these interactions reflect broader environmental issues. Employing a qualitative descriptive method, this study collects data from narrative elements—words, phrases, clauses, and sentences—found in the novel using close reading and note-taking techniques. The findings reveal multiple instances of anthropocentric behavior, in which animals are commodified and the environment is degraded to fulfill human desires. These acts not only highlight a lack of environmental consciousness but also reinforce a power hierarchy between humans and nature. The study concludes that the novel offers a critical reflection on the ethical dimensions of human–nature relationships, urging readers to reconsider their role in the ecological crisis.